Horse riding, exercise and fitness programmes: Are horse riders doing enough? - Flood, D.; Boden, E. (Journal of Human Sport & Exercise, 2017)
Horse riding is a sport which requires skill, patience and strength, however, horse riding alone does not improve the fitness of the rider extra activities and exercise programmes should be used to improve the overall fitness of the rider. The aim of this part of the study was to gain information of the lifestyle, fitness and health choices of participants. Participants (n=23) were given a questionnaire as part of a wider study, to gain information on the lifestyle, fitness regime and thoughts on horse rider fitness in the industry. The information received from the questionnaire allowed the participants to be split into groups for the study. All the answers to the questionnaire were collated and analysed in an excel spreadsheet. The results of the questionnaire showed that, 78.26% of the participants rated the importance of the horse riders fitness to be in the very important category, however only 50% of those who stated a high importance actually took part in a regular exercise programme and had a healthy diet. Of the whole participant group only 39.13% took part in a regular exercise programme when compared to the 60.87% who don`t take part in a routine exercise programme. The results of this study suggest that overall the participation of horse riders in regular exercise programmes off the horse are low, when compared to participation of the fitness training of other sports. An improvement in the participation of horse riders in fitness and exercise regimes could anecdotally reduce the risk of horse rider falls and injuries, and improve the overall sporting performance of the rider.